Shaping green regionalism : New trade law approaches to environmental sustainability - HSIEH, Pasha L. (Institutional Knowledge at Singapore Management University, 2024)
Green regionalism aims to mutually reinforce environmental governance and economic integration. The article provides the first analysis of green regionalism in international law. It argues that green regionalism represents a paradigm shift in global normative endeavours towards environmental sustainability. By contextualising three waves of global regionalism, the article unveils the evolving architecture of green regionalism alongside negotiations of the World Trade Organization and multilateral environmental agreements. Moreover, it sheds light on the pertinent disputes and features of new green initiatives galvanised by the European Union, the United States and Asia-Pacific countries. These developments are pivotal in understanding the trade-environment nexus and fostering economic resilience in our hyperconnected world.